Cost and Duration Optimization at Building C of Dharmais Cancer Hospital Jakarta with TCTO Method Using Primavera P6 Analysis - Aulia, Sahda; Setiono, Setiono; Rifai, Muji (Indonesian Journal Publisher, 2024)
In construction projects, cost and duration are important aspects but there are several factors that become obstacles. With these constraints, the project needs to organize its project management to keep it running according to the contract. The method that can be used to manage these obstacles is TCTO (Time Cost Trade Off). There are three scenarios used in this study, namely the addition of working hours, the addition of labors, and the combined (addition of working hours and labors), using the help of Primavera P6. This research aims to analyze the estimated total duration and cost obtained after optimization, compare the total duration and cost obtained before and after optimization, and recommend the most economical alternative among the scenarios carried out. The results of the optimization analysis carried out using additional working hours (scenario 1) are 611 days and an increase in costs; while with additional labors (scenario 2) are 632 days and a decrease in costs; and with combined (scenario 3) are 611 days and a decrease in costs. The most economical alternative from this study is to use scenario 2 because it reduces the duration and cost of the initial cost budget plan of the project.